The Role of Therapeutic Plasma Exchange (TPE) in Multisystem Inflammatory Syndrome in Children (MIS-C) - Gurkan Atay; Canan Hasbal; Mücahit Türk; Seher Erdoğan; Betül Sözeri (MDPI AG, 2021)
Multisystemic inflammatory syndrome in children (MIS-C) is a new potentially life-threatening disease that is related to coronavirus disease 2019 (COVID-19). The aim of this study is to reveal the clinical and laboratory results of MIS-C and the role of therapeutic plasma exchange (TPE) in its treatment. Clinical, laboratory and radiological characteristics of the patients who were admitted to the pediatric ward and pediatric intensive care unit (PICU) of a tertiary hospital with a diagnosis of MIS-C between April 2020 and March 2021 were included in the study. Forty-one patients were admitted to our hospital with a diagnosis of MIS-C. Twenty-one (51.2%) patients were admitted to the PICU. Six patients needed invasive mechanical ventilation (14.6%), 10 patients (24.4%) TPE and 3 patients (7.3%) needed extracorporeal membrane oxygenation (ECMO). The patients were grouped according to need for PICU admission (Group 1: no need for PICU, Group 2: need for PICU admission). Group 2 had significantly higher levels of C-reactive protein (CRP), alanine aminotransferase (ALT), ferritin, D-dimer, pro-B type natriuretic peptide (pro BNP) and lactate (p < 0.05). Hyponatremia found to be an independent risk factor for inpatient MIS-C in the PICU. We think that dynamic laboratory trending is beneficial in determining the need for PICU admission and TPE may be effective in critically ill patients.